2000
DOI: 10.1002/1097-0088(20000615)20:7<721::aid-joc520>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall variability in southern Spain on decadal to centennial time scales

Abstract: In this work a long rainfall series in Andalusia (southern Spain) is analysed. Methods of historical climatology were used to reconstruct a 500-year series from historical sources. Different statistical tools were used to detect and characterize significant changes in this series. Results indicate rainfall fluctuations, without abrupt changes, in the following alternating dry and wet phases: 1501-1589 dry, 1590 -1649 wet, 1650 -1775 dry, 1776-1937 wet and 1938-1997 dry. Possible causal mechanisms are discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
69
0
5

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(82 citation statements)
references
References 32 publications
8
69
0
5
Order By: Relevance
“…3). This last abrupt decadal scale change is the largest of the 1570-2005 series, coinciding with the decrease in rainfall detected on the peninsula by Rodrigo et al (1999Rodrigo et al ( , 2000, De Luis et al (2000), and Lehner et al (2006) and with the summer warming of the Central Mountains of the peninsula as from the 1980s (Raso 1997;Granados and Toro 2000;Agustí-Panareda and Thompson 2002).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…3). This last abrupt decadal scale change is the largest of the 1570-2005 series, coinciding with the decrease in rainfall detected on the peninsula by Rodrigo et al (1999Rodrigo et al ( , 2000, De Luis et al (2000), and Lehner et al (2006) and with the summer warming of the Central Mountains of the peninsula as from the 1980s (Raso 1997;Granados and Toro 2000;Agustí-Panareda and Thompson 2002).…”
Section: Discussionsupporting
confidence: 67%
“…The climate record of the last few decades shows a clear acceleration of this warming as from the 1980s (Raso 1997;Granados and Toro 2000;Agustí-Panareda and Thompson 2002;Macias et al 2006) with an apparent decrease in rainfall from the 1990s (Rodrigo et al 1999(Rodrigo et al , 2000De Luis et al 2000;Lehner et al 2006). …”
Section: Introductionmentioning
confidence: 99%
“…9a shows the evolution of the annual precipitation of the three available precipitation series (Cadiz, Gibraltar and Barcelona), the annual evolution of the observational series in Zafra and in other high resolution proxies available for this period in the Iberian peninsula built from documentary sources for Andalusia (Rodrigo et al, 1999(Rodrigo et al, , 2000 and for the south of Portugal (Taborda et al, 2004). Regarding those years with droughts influenced by volcanic activity in 1817 and 1824, all the instrumental series show that those years had precipitations lower than average, especially in Barcelona and Cadiz where precipitation records are among the driest in the whole series.…”
Section: Comparison Between Droughts Identified From Rogation Series mentioning
confidence: 99%
“…Various other studies identify dryness relationships with NAO (e.g. Rodrigo et al, 2000;Nicault et al, 2008;Santos et al, 2010). Large time scale analysis shows that a large period fluctuation of dryness and wetness has occurred in the Mediterranean area.…”
Section: E E Moreira Et Al: Are Droughts Occurrence and Severity Amentioning
confidence: 99%
“…However, Rodrigo et al (2000) performed an analysis of rainfall variability in southern Spain on decadal and centennial scales and found an alternation of wet and dry periods, with various decades of duration. They also found that rainfall anomalies in the 20th century show a behaviour similar to other periods in the past.…”
Section: E E Moreira Et Al: Are Droughts Occurrence and Severity Amentioning
confidence: 99%